Reference Values of Spatial and Temporal Gait Parameters in a Contemporary Sample of Spanish Preschool Children: A Cross-Sectional Study - Pedro Ángel Latorre-Román; Juan Antonio Párraga-Montilla; Alejandro Robles-Fuentes; Luis Enrique Roche-Seruendo; Manuel Lucena-Zurita; Marcos Muñoz-Jiménez; Daniel Manjón-Pozas; Jesús Salas-Sánchez; Filipe Almeida da Conceição; Pedro José Consuegra González (MDPI AG, 2022)
The aim of this study was to analyze the influence of age and sex on kinematic gait parameters in preschool children, and derive reference values for this population. A total of 383 preschool children (age 3-5 years; 207 girls, 176 boys) participated in this study. We used the OptoGait system to assess the kinematics of gait at a comfortable and self-determined speed. No significant differences between the sexes were found for the main gait parameters. Among the participants, there was a significant increase in double support, reductions in absolute cadence and the coefficient of variation (CV) of cadence, an increase in absolute step length (SL), and an increase in the walk ratio (WR) from 3 to 5 years of age. However, the normalized SL and normalized WR displayed a significant reduction in both sexes. Partial correlation indicated a significant association of age with SL and normalized SL, and WR. Additionally, WR showed a significant correlation with the CV of cadence. To summarize, no relevant differences in gait performance were found according to sex; however, age was found to influence gait maturation. The normative values established for Spanish preschool children can be used to monitor healthy gait development.